Is there a benefit of proximal locking screws in osteoporotic distal radius fractures? – A biomechanical study. Issue 8 (August 2016) - Bockmann, Benjamin; Budak, Can; Figiel, Jens; Lechler, Philipp; Bliemel, Christopher; Debus, Florian; Schwarting, Tim; Oberkircher, Ludwig; Frink, Michael
Abstract: Introduction: The distal radial fracture is a common fracture and frequently seen in geriatric patients. During the last years, volar plating has become a popular treatment option. While the application of locking screws at the distal fragment is widely accepted, there is no evidence for their use at the radial shaft. Materials and methods: In six osteoporotic pairs of matched human cadaver radii an extra-articular model creating an AO 23-A2.1 fracture was employed. Osteosynthesis were performed using the APTUS 2.5 Adaptive TriLock Distal Radius System (Medartis AG) with locking (LS) or non-locking screws (NLS) for proximal fixation. Biomechanical testing was performed in a staircase fashion: starting with 50 cycles at 200 N, the load was continuously increased by 50 N every 80 cycles up to a maximum force of 400 N. Finally, load to failure was analyzed with failure defined as sudden loss of force measured (20%) or major deformation of the radii (10 mm). Results: At 200 N, 250 N, 300 N, 400 N and load to failure, the NLS group showed a higher degree of elastic modulus. In contrast, the LS group showed higher elastic modulus at 350 N. Maximum force was higher in the LS group without reaching statistical significance. Reasons for loss of fixation were longitudinal shaft fractures, horizontal peri-implant fractures and distal cutting out. No difference was seen between the two groups concerning the development of the above mentioned complications. Conclusion: Our study did not show biomechanical superiority for distal radius fracture fixation by using locking screws in the proximal holes in an osteoporotic cadaver study. At load to failure, longitudinal shaft fractures and peri-implant fractures seemed to be a more relevant problem rather than failure of the proximal fixation.